Klient instytucjonalny na polskim rynku ubezpieczeniowym. Zmiany w zachowaniach w latach 1995-2005 - Mocek, Marek (Institutional Client in the Polish Insurance Market. Behaviour Changes in the Period 1995-2005, 2008)
The article presents the changes in the behaviour of business entities and institutions which use insurance services. The analyzes concern the changes observed in the period between 1995 and 2005 in the scope of the choice of insurance companies, the way of purchasing insurance and contacting the insurance companies, the number of companies the services of which the clients use, the scope of insurance covers (number of insurances, insurance groups) as well as the amount of expenditure allocated for insurance services and the value of damages and compensation paid. The analyzes were based on annual Polish field research conducted among companies and institutions by ZBM (Marketing Research Institute) "Infomarkt" and the Department of Marketing Research at the Poznań University of Economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 252-261